Self-perceived oral health in teachers with diabetes mellitus - Silva, Ângelo Fonseca; Vasconcelos, Adriele Sales Soares; Silva, Loren Stéphanie de Souza e; Neri, Anna Marina Teixeira Rodrigues; Silva, Larissa Doalla de Almeida e; Silva, Thiago Fonseca; Haikal, Desirée Sant’Ana (Seven Editora, 2024)
Objective: To analyze the association between self-perception of oral health in basic education teachers in the state of Minas Gerais with and without diabetes mellitus. Methods: An analytical cross-sectional study was conducted with secondary data from an epidemiological survey conducted in July 2020 (ProfSMoc - Minas Covid Stage), involving 1907 teachers from the state public school system of Minas Gerais. Socioeconomic and oral health variables were investigated. The collected data were tabulated using SPSS version 20.0 for Windows, and the Kolmogorov-Smirnov test was applied to evaluate the normality of the data. The chi-square test was used to analyze the associations. The level of significance adopted in the tests was 95%. Results: Among the 1907 patients analyzed, it was found that the patients' ages ranged from 21 to 72 years (mean age 44.37 years; median 44 years), 77.2% were female, 54.5% were white, and 6.2% had diabetes mellitus. A statistically significant association was observed between the variables self-perception of oral health and gender (p = 0.007), skin color (p = 0.021), family income (p = 0.000), and diabetes mellitus (p = 0.001). Conclusion: There is an association between the self-perception of oral health in basic education teachers of the state public school system of the state of Minas Gerais and the presence of diabetes mellitus. DOI:https://doi.org/10.56238/sevened2024.007-079